(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the jurisprudential school of Umar ibn Abdulaziz ibn Marwan ibn Hakam (61–101 AH / 681–720 CE), his method of ijtihad, his connection with the scholarly heritage of the Companions and Followers (tabiʿun), his experience in the practical application of Islamic jurisprudence, and his place in the history of Islamic law. Known not only as a just ruler but also as an ascetic scholar and one of the mujtahid scholars, his jurisprudential views formed under the decisive influence of the school of the scholars of Medina exercised a profound impact on subsequent Hijazi and Sunni legal thought, particularly the Maliki madhhab. The article examines his principal reforms in state administration the restoration of unjustly seized property, the abolition of unfair taxation, judicial independence, and the formal initiation of hadith collection and situates each within the framework of Islamic jurisprudential principles. It further analyzes his relationship with the four principal Sunni madhhabs and his ascetic spiritual legacy